Interfacial energy band engineered CsPbBr3/NiFe-LDH heterostructure catalysts with tunable visible light driven photocatalytic CO2 reduction capability. Issue 4 (16th January 2023) - Sun, Haoyue; Tang, Rui; Zhang, Xingmo; Zhang, Shuzhen; Yang, Wenjie; Wang, Lizhuo; Liang, Weibin; Li, Fengwang; Zheng, Rongkun; Huang, Jun
Abstract : CsPbBr3 /NiFe-LDH heterostructure photocatalysts are developed with tuneable Z-scheme reduction capability for efficient CO2 reduction performance. Abstract : To alleviate the global warming and energy crisis, it is of great urgency to develop photocatalysts with broad-range light-absorption and efficient carrier transfer for artificial photosynthesis and green chemical production. Herein, brand-new CsPbBr3 nanocrystal coupled NiFe-LDH (CPB/NiFe-LDH) Z-scheme photocatalysts are rationally constructed for efficient photocatalytic CO2 reduction. Due to the unique CPB/NiFe-LDH Z-scheme heterojunction, the photogenerated carrier transfer behaviors can be tailored with reduction active sites regulated to CPB, leading to greatly improved carrier transfer ability and energetic reduction potential compared with pristine NiFe-LDH. By further precisely controlling the CPB/NiFe-LDH ratio, tuneable Z-scheme photocatalytic reduction capability and charge separation efficiency are observed with the optimal CPB/NiFe-LDH-2 photocatalyst achieving an enhanced electron consumption rate of 39.58 μmol g −1 h −1, which is about 2 folds higher than that of pristine NiFe-LDH. This work provides an innovative approach to construct photocatalysts with tunable Z-scheme charge transfer behavior, which can also be applied to other related solar energy conversion applications.